Information-Seeking Habits of Education Faculty - Rupp-Serrano, Karen; Robbins, Sarah (My University, 2013)
This study explores the information-seeking behavior of academic education faculty from twenty large public research universities. The investigation includes an examination of how frequently education faculty seek or access information, how they stay up-to-date on current developments in the field and identify less recent journal literature, how valuable library resources and services are to their information needs, and the importance of library research to the field of education. The responses from the survey participants emphasize the importance of electronic access to scholarly journals and library databases and the continuing value of books, both print and electronic, for meeting the information and research needs of education faculty.
Keywords: Library Science.